1992
DOI: 10.1109/41.161474
|View full text |Cite
|
Sign up to set email alerts
|

Large-signal feedback control of a bidirectional coupled-inductor Cuk converter

Abstract: Under conditions of order reduction, a nonlinear control of a bidirectional coupled-inductor Cuk converter suitable for large-signal applications is presented. The converter is accurately modeled as a second-order bilinear system and the conditions established for local controllability. The integration of converter state equations and the subsequent introduction of a linear recurrence between the output variable and an external reference signal lead to a nonlinear control law that is implemented by means of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Replacing (11) in (16) Solving (17) we obtain that control ߬ሺ݊ሻ should be chosen as where ߬ ሺ݊ሻ stands for "equivalent control" which is the control law that yields the motion in the surface ‫ݏ‬ሺ‫ݔ‬ሻ ൌ 0. Substituting (12) in (19) the following expression is obtained…”
Section: B Equivalent Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing (11) in (16) Solving (17) we obtain that control ߬ሺ݊ሻ should be chosen as where ߬ ሺ݊ሻ stands for "equivalent control" which is the control law that yields the motion in the surface ‫ݏ‬ሺ‫ݔ‬ሻ ൌ 0. Substituting (12) in (19) the following expression is obtained…”
Section: B Equivalent Controlmentioning
confidence: 99%
“…For that reason, it is necessary to obtain a good discrete-time model of the system before trying to implement any discretized analog control. For that reason, the bilinear recurrence in [19] for converters that operate in PWM and continuous conduction mode (CCM) has been taken as the starting point.…”
Section: Bilinear Discrete-time Model Of the Boost Convertermentioning
confidence: 99%
“…It can be observed that, although the equation corresponding with the voltage regulator is linear, Equations (17), (19), (26) should be linearized around the equilibrium point so that the choice of coefficients k 1 , k 2 or k n , β can be carried out by means of linear control techniques. The analysis of the linearized equations together with Equation (35) in the z domain results in the following transfer equations…”
Section: Voltage Regulationmentioning
confidence: 99%
“…This has the advantage of simplifying the control implementation with respect to the hybrid control realizations found extensively in the literature. The starting point of the controller proposed in this article is the bilinear recurrence developed in [26] for PWM converters in CCM, which is reviewed in Section 2. The proposed nonlinear controller is obtained by input-output linearization and presented in Section 3, in which a discrete-time sliding mode interpretation is also provided.…”
Section: Introductionmentioning
confidence: 99%
“…where is given by (17). The equilibrium point of (19)- (22) results from the intersection of the curve of equilibrium points and the discontinuity surface. Namely, (27) and therefore will be given by (28), shown at the bottom of the page, or if and…”
Section: Sliding Domainmentioning
confidence: 99%